A Study on the Influence of “Shadow Education” about the Students’ Achievements Moderated by the Parents' Expectations in China - Fengjun QI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
“Shadow education”, also known as “tutoring” or “private tutoring”, is a kind of education style outside of the mainstream official school education, and constantly changes along with the school education above mentioned, it’s same as the shadow keeps close to the body, so just called “shadow education”. When there are more advocations of reducing the learning burden of the schoolchildren last several years, but on the other hand the demands for“tutoring ” have soared in China astonishingly. Because the supplies of “shadow education” is supported practically from the parents in China,this study researches for the influence of “shadow education” about the schoolchildren’s achievement moderated by the parents' expectation, by the ways of the adoption of the data from 2013 to 2014 on Chinese family dynamic tracking from the database of ChineseFamilyPanelStudies( CFPS) ,also continuly uses “sample regression” and “threshold effect” to analysis, the conclusions of this study are,it’s a significant impact between “shadow education” expenditure and the schoolchildren’s academic performance, the shadow education expenditure increase1,000 RMB, schoolchildren’s academic performance can increase relatively 0.246 standard deviations. The sample regression about the moderating effect shows there is a moderating effect between the parental education expectations and the schoolchildren’s academic performance, shows a positive moderating effect on the whole.The older schoolchildren have the better performances and the greater effects from the shadow education,also the older the schoolchildren are, the better their grades will be, there are threshold effects between the parental education expectations and the schoolchildren’s academic performance generally. The results of the “threshold regression” based on the “threshold value “, show that when parents' educational expectations are greater than the “threshold value” and the parents' expectations are less than the “threshold value”, “shadow education” expenditures have a significant positive impact on the schoolchildren’s academic performance, but the parents' expectations are less than the “threshold value” of the “sample regression”, the coefficient is greater, the degrees of positive influence are more greater. It’s obviously different “shadow education” expenditure on the schoolchildren’s academic performance between urban and rural ,there are the increase in parental education expectations has a greater moderating effect on increasing “shadow education” expenditures to improve the schoolchildren’s academic performance in rural areas. It is also found that “shadow education” expenditures will improve the schoolchildren’s academic performance , the parental education expectations also give play to positive regulatory effects on the input & output of “shadow education” too. “shadow education”and “school education”still keep a certain complementary effects in this time.Finally,this study will put forward some opinions & suggestions for the governments, schools, families in China.